Krótki zarys przemian kulturowych w środkowej i późnej epoce brązu w międzyrzeczu Bzury i Pilicy - Wiklak, Henryk (Acta Universitatis Lodziensis. Folia Archaeologica, 1992)
Cultural changes that occurred in Central Poland in the Middle and Late Bronze Age were the reflection of general processes that were taking place at that time all over Poland and Central Europe as well. After having abandoned the use of stone the people were learning to use bronze instead. This, in turn, brought about changes in cultural and social relations current so far. In Central Poland where no bronze was available the changes were much slower being impeded by various internal and external factors. At that time Central Poland was settled by people of the Central Polish group of the Lusatian culture. The changes were affecting both house construction and burial rite where the custom of cremating and burying the dead either in single urn graves or in unurned pit burials became prevalent. Also everyday objects, eg. pottery, had stylistically changed. By the end of the Bronze Age stone tools virtually stopped to be used. In the Late Bronze Age the development of Lusatian settlement of the Central Polish group slowed down. Its revival took place in the Early Iron Age, however, it was of only a short duration. Besides, it is not the subject of the present paper.